Weathering The Storm – Icelandic Municipalities’ Handling of an Unprecedented Economic Crisis - Magnús Árni Skjöld MAGNÚSSON (Strategic Public Management Journal, 2016)
Within a few days in October 2008, following serious turmoil on financial markets worldwide, some 85% of the Icelandic banking sector collapsed, together with the Icelandic currency, the króna. Almost all the rest followed early in 2009. The Icelandic stock market took a nosedive. The Republic of Iceland had entered the worst economic crisis of its history. Icelandic municipalities, which had taken on an increasing burden of running the welfare state, were hard hit financially, without the ability of the state to help out. In fact, some of the post-crisis actions of the state, under IMF direction, were difficult for the municipalities. It did not make things easier that the crisis had been precluded by an unprecedented period of growth, encouraging the municipalities to borrow in international markets and invest in infrastructure that turned out to be superfluous in the post-crisis period. This paper will look at the reactions of the Icelandic municipalities to the crisis, the political implications of it, where they are now and if there are lessons that can be learned from the difficult years in the last decade.